Silver nanoparticles induce a non-immunogenic tumor cell death - Garcia-Garcia M. R. Maritza Roxana; Casares N. Noelia; Martinez Perez L. A. Luz Andrea; Juarez C. E. Curiel Efren; Hernandez A. A. J. Andres Alberto de Jesus; Bogdanchikova N. Nina; Garibo D, Diana; Rodriguez-Hernandez A. G. Ana; Pestryakov A. N. Aleksey Nikolaevich; Castro Gamboa S. Sandra; Arias Ruiz L. F. Luis Felipe; Torres Bugarin O. Olivia; et al. (2023, 2023)
Title screen